Fine-dining in Prisons: Online Tripadvisor Reviews of The Clink Training Restaurants - Gebbels, Maria; McIntosh, Alison; Harkison, Tracy (Elsevier, 2021)
This study evaluated customer reviews about The Clink restaurants to understand how they are rated and what experience is gained by fine dining in a prison. The Clink Charity runs training restaurants in four U.K. prisons and aims to change attitudes and transform lives through prisoner rehabilitation. This research used an interpretive case study of the Clink restaurants to evaluate online customer reviews posted on TripAdvisor. In total, 3951 reviews were analysed using Leximancer 5.0. The most prominent themes were Food: ‘fine-dining in prisons’, Visit: ‘The Clink ambassadors’, and Prison: ‘the inside and outside divide’. Despite the prison location, customers reported having exceptional, professional and memorable dining experiences delivered by highly trained chefs, and that the front of house staff would rival those in many fine-dining restaurants. Further research is required to confirm how dining at a Clink restaurant may have potentially begun to change the public perceptions of prisoners.
Keywords: Prisons; Hospitality industry; Training restaurants; Leximancer; TripAdvisor; Customer reviews